THE ANALYSIS OF WARUNG NASI'S MARKETING MIX STRATEGY IN THE FACE OF COMMERCIAL COMPETITION (CASE STUDY BY WARUNG NASI MAMA MIA, DANGDEUR, BANDUNG) - Yudistia Teguh Ali Fikri (Journal of Business Administration, 2023)
In starting a business, the marketing mix strategy is one of the crucial aspects. The business landscape is highly competitive, requiring effective marketing strategies to achieve planned outcomes and gain a competitive edge in the market. Therefore, research on marketing mix strategies from an Islamic economic perspective is essential. In light of this background, business operators must consider marketing mix strategies that align with the principles of Islamic economics to compete effectively while adhering to Islamic principles.The research problem in this study is to examine the marketing mix strategy of Mama Mia Nasi Goreng (Fried Rice) stall in facing business competition and assess whether the marketing mix strategy aligns with Shariah (Islamic law) principles. The objective is to identify the marketing strategies employed by Mama Mia Nasi Goreng stall and evaluate their conformity to Shariah business principles. Data for this research were obtained through interviews, observations, and documentation. The findings of this study reveal that Mama Mia Nasi Goreng stall employs a marketing mix strategy, commonly known as the 4Ps (product, promotion, price, place). The stall emphasizes product quality, promotional activities, pricing, and location. The marketing strategy adopted by Mama Mia Nasi Goreng stall adheres to the principles of Islamic business, namely siddiq (honesty), amanah (trustworthiness), tabligh (communication), and fathonah (wisdom). However, the weaknesses observed in Mama Mia Nasi Goreng stall's implementation of its marketing strategy are a lack of consistency in promotional activities and limited parking space.